(3QSGdI aj JMbjb fhYi GdMUhds - (3CMeO Hf SdjeGf Hf ceGd HGTG GdQhej , TeS GdOjf,J (B940 (3g` s
(3ChdgG (B:s
(3GdMeO dhdjg hGdUdGI Ydi fHjg hHYO agPg QSGdI eYehdI ai JMbjb fhYi GdMUhd eG Ydi SHjd GdJOQjL heGdG Ydi SHjd GdJOQjL aEfg eRdg GdGbOGe heVdI GdGagGe s
(3BNQgG (B:s
(3Ef ebOGQ eG djS HehLhO dGjchf ehLhO dGjchf SehLhOkG aGQJcHhG ai JhLjg eGRHQ ai cJH GdMceI ef CfgG ef bHjd Gdce GdeJUd JeJ GdQSGdI dGHf ceGd HGTG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B1s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B133 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B1 - (3U (B238 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B141s
Keywords: (3GdJhMjO hGdedd hGdfMds